ASSISTANCE IN QUR’ANIC READING DEVELOPMENT USING THE JIBRIL METHOD AT NURUL JADID ISLAMIC BOARDING SCHOOL, ZAID BIN TSABIT REGION (K) - Abd. Basid; Fadoilur Rohman; Ilyas; Moh Bayu Bahtiar Ramadhani; Moh Hafidul Ahkam; Syarif Hidayatullah; Misbahul Arifin (International Journal of Multidisciplinary Reseach, 2025)
This community service program was motivated by the suboptimal implementation of Qur’anic reading instruction in the Tahsinul Qirā’ah Program at Nurul Jadid Islamic Boarding School, Zaid bin Tsabit Region, particularly regarding the incomplete, unstructured, and undocumented application of the Jibril Method. The focus of this program was to provide assistance in Qur’anic development through the ideal implementation of the Jibril Method based on a khatam system, accompanied by the strengthening of a sustainable recitation evaluation framework. The objectives were to improve students’ Qur’anic reading quality, enhance learning motivation, and support the timely achievement of program graduation targets. The program employed a participatory action research (PAR) approach, utilizing participatory observation, Qur’anic reading pre-tests and post-tests, documentation of students’ recitation progress, and interviews with program administrators and asatidz. The results indicate significant improvements in students’ recitation quality, increased awareness of recitation errors, and positive changes in learning motivation and discipline. The implications of this community service highlight the importance of integrating traditional pesantren talaqqī methods with structured learning evaluation systems as a strategy for the sustainable enhancement of Qur’anic learning quality.